Forty years of theo-mission education in Eastern Africa: The case of St. Andrew's Kabare, Kenya (1977-2017) - Gathogo, Julius Mutugi (Stellenbosch theological journal, 2017)
The article seeks to explore the intrigues behind the establishment of St Andrew's College of Theology and Development in Eastern Africa, at the Kabare Hill of Kenya, from May 1977. How does the legacy of the pioneer European missionaries to Eastern Africa (I refer to Krapf, Hannington, Tucker, Parker, McGregor, Crawford, Beecher among others) contribute to the current state of affairs in mission education and the establishment of St. Andrew's College in particular? The materials in this article are largely gathered through extensive reading of relevant literature, face-to-face interviews, oral sources and archival sources. The article coincides with the 40th anniversary celebration of St Andrew's College, Kabare - that began in 1977 as an institute for mission and evangelism. Through showcasing St Andrew's, the article has methodologically revisited the 19th and 20th European missionary legacy that inspired the current growth of the church in Eastern Africa. In turn, it has established that despite the gains so far made, there is still room in authenticating theological education in Eastern Africa and the rest of the tropical Africa.